HIV viral suppression in the era of dolutegravir use: Findings from a national survey in Tanzania - Kamori, Doreen; Barabona, Godfrey; Maokola, Werner; Rugemalila, Joan; Mahiti, Macdonald; Mizinduko, Mucho; Sabasaba, Amon; Ruhago, George; Mlunde, Linda; Masoud, Salim S.; Amani, Davis; Mboya, Erick; et al. (PloS one, 2024)
Tanzania has made significant progress in improving access to HIV care and treatment. However, virologic suppression among people living with HIV (PLHIV) has not been fully realized. In March 2019, Tanzania introduced a World Health Organization (WHO)-recommended dolutegravir-based regimen as the default first-line regimen. Eighteen months later we investigated the HIV viral suppression rates and the factors associated with lack of viral suppression among PLHIV (children and adults) in Tanzania. A cross-sectional survey was conducted from September to December 2020 among PLHIV on antiretroviral therapy (ART) in Tanzania. Whole blood samples, demographic data and clinical information were obtained from eligible adults (≥15 years) and children (< 15 years) attending thirty-six HIV care and treatment centres located in 22 regions of Tanzania mainland. A whole blood sample from each participant was processed into plasma and HIV viral load was estimated using real-time PCR. HIV viral suppression was defined at a cut-off of < 50 copies/mL as recommended by WHO. Analyses were conducted using descriptive statistics to establish the national representative prevalence of viral suppression, and logistic regression analyses to determine independent factors associated with non-suppression. A total of 2,039 PLHIV on ART were recruited; of these, adults and children were 57.5% (n = 1173) and 42.5% (n = 866), respectively. Among the adult population, the mean age and standard deviation (SD) was 42.1 ± 12.4 years, with 64.7% being female. Among children, the mean age and SD were 9.6 ± 3 years, and 53.2% were female. Overall viral suppression at < 50 copies/mL (undetectable) was achieved in 87.8% of adults and 74.4% of children. Adults and children on dolutegravir-based regimen recorded viral suppression rates of 89.7% and 85.1% respectively. Factors independently associated with lack of viral suppression status in the adult population were age and ART adherence while in the children population, the factors were sex, ART adherence, and current ART regimen (p<0.05). Dolutegravir-based regimens are promising to help attain epidemic control in Tanzania. More efforts especially on ART adherence are needed to attain optimal treatment outcomes for children and adults PLHIV in Tanzania.